Molecular mechanisms of human herpes viruses inferring with host immune surveillance. Issue 2 (2nd July 2020) - Jasinski-Bergner, Simon; Mandelboim, Ofer; Seliger, Barbara
Abstract : Several human herpes viruses (HHVs) exert oncogenic potential leading to malignant transformation of infected cells and/or tissues. The molecular processes induced by viral-encoded molecules including microRNAs, peptides, and proteins contributing to immune evasion of the infected host cells are equal to the molecular processes of immune evasion mediated by tumor cells independently of viral infections. Such major immune evasion strategies include (1) the downregulation of proinflammatory cytokines/chemokines as well as the induction of anti-inflammatory cytokines/chemokines, (2) the downregulation of major histocompatibility complex (MHC) class Ia directly as well as indirectly by downregulation of the components involved in the antigen processing, and (3) the downregulation of stress-induced ligands for activating receptors on immune effector cells with NKG2D leading the way. Furthermore, (4) immune modulatory molecules like MHC class Ib molecules and programmed cell death1 ligand 1 can be upregulated on infections with certain herpes viruses. This review article focuses on the known molecular mechanisms of HHVs modulating the above-mentioned possibilities for immune surveillance and even postulates a temporal order linking regular tumor immunology with basic virology and offering putatively novel insights for targeting HHVs.